PEMANFAATAN UAV UNTUK MENDUKUNG PERTAHANAN UDARA IKN NUSANTARA SEBAGAI CENTER OF GRAVITY - Andi Fathurrachman Batara Sulo; Romie Oktovianus Bura; Sovian Aritonang (Jurnal Education and Development, 2022)
The transfer of the capital ushered in a new geostrategic era. Nevertheless, the strategic location of IKN cannot be separated from the threat of defense and security disruptions carried out by state actors, non-state actors, and hybrids. This research aims to analyze the Utilization of UAVs Supporting the Air Defense of the National Capital (IKN) Nusantara as a Center of Gravity. Qualitative research methods with literature studies are used in this article. The results of the study revealed that to secure the nation's capital, air defense units must be added to vital locations. This is done by developing airbases of each province that need to be mobilized with ground forces and deploying fighter forces, and UAVs. Maximum airspace security is necessary to maintain sovereignty in the airspace because without it sovereignty will be threatened by aviation attacks from third parties. On the other hand, stakeholders are also expected to be ready, including governments, experts, and the media, which have a vital role in shaping public perceptions and perceptions of potential threats based on regional characteristics. In addition, considering that society is an actor who plays a very role in the defense and security of the country, it is known as the universal people's defense system (sishankamrata).